2017
DOI: 10.1016/j.ejvs.2017.02.023
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Analysis of Healthy Aortic Arch

Abstract: CT images from 123 subjects (mean ± SD age 53 ± 19 years) were reviewed. Significant correlation between age and morphology was found. The aorta expanded homogeneously and stretched heterogeneously with age because of posterior arch elongation. TI decrease, CR, and attachment zone angle increase were also observed with aging. Age remained significantly associated with these morphological parameters, independently of body surface area and hypertension. Sex also affected morphology: longer total arch length and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(26 citation statements)
references
References 20 publications
1
24
0
1
Order By: Relevance
“…Imaging analyses for the parameters of the aortic arch and carotid artery were similar to those described in the literature. 9,11 Carotid and aortic length and angulation were directly calculated in the sagittal and coronal planes. Carotid and aortic length were defined as the curvilinear distance between the vessel origin and end.…”
Section: Anatomic Measurement Protocolmentioning
confidence: 99%
“…Imaging analyses for the parameters of the aortic arch and carotid artery were similar to those described in the literature. 9,11 Carotid and aortic length and angulation were directly calculated in the sagittal and coronal planes. Carotid and aortic length were defined as the curvilinear distance between the vessel origin and end.…”
Section: Anatomic Measurement Protocolmentioning
confidence: 99%
“…Aortic morphology has been reported to be associated with age. A study of 123 subjects without thoracic aorta pathology or surgery found that the aortic diameter enlarges, the posterior arch elongates, the tortuosity index decreases, and the attachment zone angle is larger in older people [1]. Age had a correlation coefficient of 0.61 with arch length (p < 0.01) in the study.…”
Section: Introductionmentioning
confidence: 63%
“…The percentage of patients showing elongation at the STJ-INA segment during the follow-up was 2%, 5%, 12%, 15%, and 20% at the first, second, third, fourth, and fifth year follow-up (Table 4). 1 The data are presented as the number of patients showing lengthening of the aortic segment of 10 mm or more, which was classified as having elongation. STJ: sinotubular junction; INA: innominate artery; LCCA: left common carotid artery; LSCA: left subclavian artery; CA: celiac artery.…”
Section: Elongationmentioning
confidence: 99%
“…Third, the human arch anatomy has significant morphological differences. 20 The unibody branched stent grafts have to be custom-made for apparent anatomical variability. Finally, the introducer sheath applied to human patients could be 22e24F and so the diameter of the stent graft system should be further decreased in future studies.…”
Section: Discussionmentioning
confidence: 99%